Kepuasan Kerja dan Komitmen Organisasi pada Satuan Polisi Pamong Praja (Satpol PP) Kabupaten Jayawijaya: Bukti Empiris dan Arah Kebijakan Sumber Daya Manusia - Soltan Takdir; Sarni Brabar; Hasriani Muslim (PIRSAP (Paser Institute for Scientific Research and Publications), 2025)
This study examines whether job satisfaction predicts increased organizational commitment among civil servants in a regional regulation enforcement agency, the Jayawijaya Regency Public Order Agency (Satpol PP). The research method used was an associative quantitative approach. The population of the study was 86. Purposive sampling was used to obtain a sample size of 47 individuals. The analysis methods used were descriptive analysis, simple linear regression, t-test, and coefficient of determination. The results showed that job satisfaction positively and significantly influenced organizational commitment among Satpol PP Jayawijaya Regency employees